Determination of antioxidant and anti-inflammatory properties of Salvia aethiopis/sclarea and synthesized silver nanoparticles (Annals of Medical Research, 2024)
Aim: In the study, the phenolic compounds of Salvia aethiopis/sclarea will be determined and the antioxidant and anti-inflammatory activities of the extracts of these plants and the synthesized silver nanoparticles (AgNP) will be examined in vitro.Materials and Methods: Extracts obtained from Salvia spp. (SE) collected from the Kyrenia region of Cyprus were used in the study. Methanol extracts were prepared and total phenolic, flavonoid and alkaloid contents were determined. The amount of phenolic compounds was then quantified and identified using HPLC. The antioxidant properties of Salvia aethiopis/sclarea were analyzed using various markers, including lipid peroxidation inhibition activity, 1,1-Diphenyl-2-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) scavenging capacity. Additionally, their anti-inflammatory effects were investigated by proteinase inhibitor activity, heat-induced hemolysis and albumin denaturation analyses.Results: S. aethiopis and S. sclarea were contained high levels of the phenolic compounds isoquercetin and caffeic acid or naringenin and caffeic acid, respectively. After green synthesis of silver nanoparticles, the antioxidant and anti-inflammatory properties of plant extracts increased significantly (p
Keywords: Salvia aethiopis; Salvia sclarea; Phenolic; Green synthesis; Antioxidant; Anti-inflammatory